2019
DOI: 10.1080/2162402x.2019.1708066
|View full text |Cite
|
Sign up to set email alerts
|

In the mix: the potential benefits of adding GM-CSF to CpG-B in the local treatment of patients with early-stage melanoma

Abstract: Whereas TLR9 agonists are recognized as powerful stimulators of antitumor immunity, GM-CSF has had mixed reviews. In previously reported randomized trials we assessed the effects of local immune modulation in early-stage melanoma with CpG-B alone or with GM-CSF. Here we discuss the added value of GM-CSF and show sex-related differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
(43 reference statements)
1
6
0
Order By: Relevance
“…Local administration of ICI has been described in pre-clinical models and tested in several types of cancer in clinical trials by us and others, with positive results (42,(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70). We reported that peritumoral delivery of anti-CTLA-4 in mouse models resulted in an equally efficient antitumor response as observed after systemic administration, without the usually associated inflammatory side effects (65).…”
Section: In Conclusion: the Rise Of Local Immunotherapymentioning
confidence: 79%
“…Local administration of ICI has been described in pre-clinical models and tested in several types of cancer in clinical trials by us and others, with positive results (42,(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70). We reported that peritumoral delivery of anti-CTLA-4 in mouse models resulted in an equally efficient antitumor response as observed after systemic administration, without the usually associated inflammatory side effects (65).…”
Section: In Conclusion: the Rise Of Local Immunotherapymentioning
confidence: 79%
“…112 Corroborating initial findings, the intratumoral or systemic administration of DMXAA or other STING agonists, alone or combined with other therapeutic agents, have ultimately been attributed pronounced therapeutic effects in numerous murine models of fibrosarcoma, glioma, 80 melanoma, 66,113 as well as breast, 114-117 colorectal 118 and prostate carcinoma. 119 Moreover, various CDNs have been shown to boost the therapeutic activity of anticancer vaccines in a variety of tumor models, including (1) mouse 4T1 triple-negative mammary carcinomas treated with a Listeria monocytogenes-based vaccine; [120][121][122] (2) mouse B16 melanomas treated with the TRIVAX vaccine, which consists of synthetic peptides, the Tolllike receptor 3 (TLR3) agonist polyinosinic:polycytidylic acid (polyI:C) 123 and co-stimulatory antibodies 124,125 targeting CD40, 126 or the STINGVAX vaccine, a cellular vaccine engineered to secrete colony-stimulating factor 2 (CSF2, best known as GM-CSF), 127 plus an immune checkpoint blocker targeting programmed cell death 1 (PDCD1, best known as PD-1), [128][129][130] and (3) mouse CT26 colorectal carcinoma treated with the STINGVAX vaccine plus a PD-1 blocker. 128,130 However, natural CDNs are rapidly degraded by circulating and cell-bound enzymes, including ectonucleotide pyrophosphatase/phosphodiesterase 1 (ENPP1), 131 calling for the development of molecules with improved stability for clinical applications.…”
Section: Sting Signaling In Preclinical Tumor Modelsmentioning
confidence: 99%
“…Total RNA was isolated from PBMC and reverse transcribed as previously described. 18 Forty-seven type I IFN response genes (IRGs) were selected based on significant upregulation in more than three experiments published on the Interferome database ( http://www.interferome.org/ ). Custom-designed TaqMan assays for each IRG were supplied by Applied Biosystems.…”
Section: Methodsmentioning
confidence: 99%